47.8k views
4 votes
Solve 2y + xy = 6for y. Then find the value of y when x = -3

1 Answer

2 votes
This is the method of substitution in Algebra.
You would plug the number that they gave you into the fraction. In this case that number is -3
You then get this equation,
2y+(-3)y = 6
This then becomes,
2y-3y=6 because of distributing the negative.
2-3 = -1 which is combining your like terms.
-y=6
Divide by -1 to get rid of the negative(-) by the y.
Your answer is -6
Hope this helped.
User Nulik
by
5.1k points